Easy fabrication of a novel electro-spun PVDF-g-C3N4-Pd nanocomposite material as improved anode electrocatalyst for direct alcohol fuel cell. (15th September 2022) - Chokkiah, Bavatharani; Wabaidur, Saikh Mohammad; Siddiqui, Masoom Raza; Islam, Md Ataul; Dhanusuraman, Ragupathy; Ponnusamy, Vinoth Kumar
Graphical abstract: Highlights: A simple, effortless one-step electrospinning process to prepare a high-performance electrocatalyst. Physicochemical results authenticate Poly(vinylidene fluoride)- graphitic carbon nitride/palladium nanocomposite fibers. PVDF-g-C3 N4 -Pd electrocatalyst for excellent methanol and ethanol electro-oxidation process. Reliable mechanical and good thermal stability. A platform for future research directions in electrospun nanofiber development and DAFCs applications. Abstract: In this study, we account a simple, effortless one-step electrospinning process to prepare high-performance poly(vinylidene fluoride)- graphitic carbon nitride/palladium (PVDF-g-C3 N4 -Pd) nanocomposite fibers (NCFs) for methanol and ethanol electro-oxidation process. As-synthesized PVDF-g-C3 N4 -Pd NCFs were examined to ensure its physicochemical assets such as surface morphology, structural geometry, elemental structure, and thermal stability. The acquired long and continuous NCFs morphology with elemental and structural results authenticates the successful fabrication of PVDF-g-C3 N4 -Pd NCFs. Holding to the substantial synergistic effects of each component in the PVDF-g-C3 N4 -Pd NCFs electrocatalyst displays forward peak current densities as high as 0.53 mA/cm 2 and 10.50 mA/cm 2 for methanol and ethanol electro-oxidation reactions, respectively, far outperforming than PVDF-g-C3 N4 NCFs electrocatalyst. Also, PVDF-g-C3 N4 -Pd NCFs exhibit reliable mechanical stability and as well as thermal stability and could possibly open up an excellent high-performance portable fuel cell system for DAFCs application.